Muhammadiyah Community and Pluralism of Legal Inheritance: The Harmonization on Wealth Distribution of Javanese People - Zuhdi, Syaifuddin; Dimyati, Khudzaifah; Astuti, Widi; Hakim, Abdul; Niami, Mutimatun; Saputro, Muhammad Andi (Sakina: Journal of Family Studies, 2025)
This study is expected to provide new contributions to the study of inheritance law, especially by highlighting how Muhammadiyah members respond to legal pluralism in Indonesia. This study can help explain how this modernist Islamic organization negotiates the inheritance law amidst the diversity of legal systems in force in Indonesia. This research used the non-doctrinal research method. The harmonization of inheritance wealth division in the Javanese society, especially in Jatinom, which is mostly affiliated with the Muhammadiyah organization, reflects an integration between local wisdom and religious teachings based on the maslahah principle. The wealth division before or after the decedent’s death aims to maintain family welfare, prevent conflicts, as well as guarantee the fulfilment of heirs’ rights. This practice is not only valid according to the Sharia but is also just and flexible, as it is adapted to the actual needs of the family. This is to create a harmony that pays attention to the family’s worldly and spiritual needs.